Measures for Future Environmental Protection: Monitoring PM10 Dust Particles and Compounds – A Case Study of the Salonit Anhovo Cement Plant - Vončina, Ernest (Medicine, Law & Society, 2024)
The paper deals with the view of environmental legislation regarding ambient air quality. We are faced with different views from the legal, medical and chemical professions on the environmental and health impacts that cement-co-incinerators could have. The emission monitoring of the cement plant must be in accordance with existing legislation and regulations. The co-incineration of waste used as a secondary fuel requires that the cement kiln operates in accordance with “best available technology, BAT” and that it must not exceed the permitted emission values. In addition to the emission monitoring from the cement plant or incinerator, the monitoring of ambient air emissions should also be well established, as it indicates the ambient air quality. The emission concentrations of various pollutants found in the air or on dust particles with a diameter below 10 µm and 2.5 µm (PM10 and PM2.5) are significant. Knowledge about the detailed chemical composition of respiratory dust particles is essential in determining health impacts, as the organism’s biological response to aerosols is not always related to the most abundant compounds, but rather to the toxicologically significant ones present in trace amounts.